Indexes of spatio-temporal change to reconstruct the historical evolution of a coastal region: case study: São Sebastião Island - SP (Brazilian Journal of Oceanography, 2010)
The coastal regions of Brazil have lost most of their distinct characteristics due to an intense, diverse, and long history of land use. The current scenario is the result of successive changes which have taken place since the colonization of Brazil. These changes should be taken into account in environmental planning since the decisions about the future depend on the understanding of past changes. In this regard, the aim of this study was to identify and quantify the spatio-temporal changes in land use in a coastal region, using principles of landscape ecology and scenario construction. The case study was the São Sebastião Island, divided into 61 watersheds, off the northern coast of São Paulo State (Brazil). The study involved the development and application of a methodology to interpret the historical dynamics of the island. The driving forces were identified and indexes of change were calculated to define the phases of occupation of the island. Five phases of occupation of the coastal landscape were mapped: preservation, conservation, regeneration, exploitation and urbanization. These phases represent a pattern of internal heterogeneity, sometimes positive (environmental conservation), and sometimes negative (environmental degradation).